2013
DOI: 10.3390/md11020551
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Structural Elucidation of Chondrosterins F–H from the Marine Fungus Chondrostereum sp.

Abstract: The marine fungus Chondrostereum sp. was collected from a soft coral of the species Sarcophyton tortuosum from the South China Sea. Three new compounds, chondrosterins F–H (1, 4 and 5), together with three known compounds, incarnal (2), arthrosporone (3), and (2E)-decene-4,6,8-triyn-1-ol (6), were isolated. Their structures were elucidated primarily based on NMR and MS data. Incarnal (2) exhibited potent cytotoxic activity against various cancer cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 10 publications
(12 reference statements)
2
45
0
Order By: Relevance
“…Recent studies revealed that the cryptic biosynthetic pathways of fungi can be activated and the chemical diversity of their metabolites can be maximized by alternating their cultivation parameters systematically, such as the components of the media [1,2], co-culture [3,4], feeding precursors [5,6] and the addition of enzyme inhibitors [7,8]. For example, marine fungus Chondrostereum sp., which was isolated from soft coral Sarcophyton tortuosum , grows in different culture media and can produce various novel bioactive hirsutane-type sesquiterpenoids [9,10,11,12]. …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies revealed that the cryptic biosynthetic pathways of fungi can be activated and the chemical diversity of their metabolites can be maximized by alternating their cultivation parameters systematically, such as the components of the media [1,2], co-culture [3,4], feeding precursors [5,6] and the addition of enzyme inhibitors [7,8]. For example, marine fungus Chondrostereum sp., which was isolated from soft coral Sarcophyton tortuosum , grows in different culture media and can produce various novel bioactive hirsutane-type sesquiterpenoids [9,10,11,12]. …”
Section: Introductionmentioning
confidence: 99%
“…Incarnal extracted from G. incarnatum and another fungus in Cyphellaceae (Chondrostereum sp.) also shows potent cytotoxicity against several cancer cell lines [8,55]. To further investigate the biosynthesis of terpenoids in G. incarnatum, we mapped 35 proteins to 17 enzymes in the "terpenoid backbone biosynthesis" (KEGG: ko00900) pathway, and 10 proteins to four enzymes in the "sesquiterpenoid and triterpenoid biosynthesis" (KEGG: ko00909) pathway ( Figure 4).…”
Section: Secondary Metabolites and Terpene Pathwaymentioning
confidence: 99%
“…Secretory proteins were predicted using SignalP 3.0 [54]. Transmembrane proteins were predicted by TMHMM [55]. Protein localization signals, excluding those related to the plastid location, were identified using TargetP [56].…”
Section: Secretory Protein Analysis and Pathogenicity-related Genesmentioning
confidence: 99%
“…Our primary objective is to search for chemotherapeutic agents for prevalent malignancies with remarkably high incidence in South China, such as nasopharyngeal carcinoma and hepatocellular carcinoma. As a result, we obtained a series of cytotoxic metabolites, for example hirsutanol A [18], incarnal [19], chondrosterins A and J-M [20][21][22], pseudaboydin A [23], xanthocillin X dimethyl ether [24], 7-deacetylpyripyropene A [25], pyripyropene O [25], 13-dehydroxypyripyropene A [25] and 3,3 -cyclohexylidenebis(1H-indole) [26]. As part of our continuous project, culture of the fungus Monascus ruber BB5 with liquid GPY culture medium led to the isolation of three new compounds, monarubins A-C (1, 6 and 13), together with ten known metabolites (2-5 and 7-12) ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%